The non-coding RNA BC1 regulates experience-dependent structural plasticity and learning - Victor Briz (Nature Portfolio, 2017)
Brain cytoplasmic (BC1) RNA is a non-coding RNA that has been implicated in translational regulation, seizure, and anxiety. Here, the authors show that in the cortex, BC1 RNA is required for sensory deprivation-induced structural plasticity of dendritic spines, as well as for correct sensory learning and social behaviors.